An interdisciplinary approach to examining the working conditions of women coaches - Allen, J. B.; Shaw, S. (International Journal of Sports Science and Coaching, 2013)
An interdisciplinary framework allowed psychological and sociological approaches to be combined to examine coaches' working conditions, specifically to examine the structural aspects and social values within the sport organisations as well as the implications for individual aspects. Ten participants from two sport organisations took part in the study. They were eight women performance coaches and two coach managers. Participants were interviewed to explore their perceptions of the working environment in their sport organisation including involvement, support, opportunities, and relationships. Four themes were developed characterising coaches' perceptions of their working conditions. These were relationships with key organisational personnel, coach as a person, learning and development opportunities, and relationships among coaches. The themes were examined both within and between the two sport organisations. The structures and values of one organisation fostered working conditions conducive to the need satisfaction of the coaches. The working conditions within the second organisation were less effective, but reflected its organisational values. The findings are discussed in relation to coaching research and provide an alternative approach to examining the social context of coaching.